Полупроводниковый шим-коммутатор для системы безредукторного привода пассажирского лифта на базе бесколлекторного двигателя постоянного тока с дисковым ротором - Бибик, Артур Витальевич (НТУ "ХПИ", 2010)
In-process talked about creation of 4-th quadrant semiconductor PWM – switchboard and three-contour system of adjusting, which together with the commutatorless motor of direct-current with a disk rotor it is possible to use in an lift gearless electric drive. It will allow to promote reliability, simplify service, and due to enhanceable coefficient of useful effect - to economize electric power in static and dynamic modes. The flow diagram of switchboard is resulted. The experimental oscillograms of voltage and current are presented.
Semiconductor PWM–switchboard for system of gearless drive of passenger lift on base of commutatorless motor of direct-current with disk rotor
Keywords: электропривод; статор; обмотка якоря; ротор; ток постоянный